Emotional Exhaustion and Family Support in the Link Between Transactional Leadership and Crew Retention - Nazarwin; Rusdi, Rino; Abror; Putra, Riki Wanda (Ilomata International Journal of Management, 2026)
This study examines how transactional leadership (TL) influences the retention intention (RI) of Indonesian seafarers through the mediating role of emotional exhaustion (EE) and the moderating effect of family support (FS). The research uses the Job Demands–Resources (JD–R) model to explain how excessive supervision, strict compliance, and punitive control can increase psychological strain and emotional fatigue. Data were collected from 298 crew members working on medium-sized vessels operated by national shipping companies and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that TL positively affects EE (β = 0.292, p < 0.001) and indirectly reduces RI (β = 0.037, p = 0.018), while maintaining a direct positive impact on RI (β = 0.317, p < 0.001). EE partially mediates the TL–RI relationship, suggesting that emotional fatigue can lead to “forced retention” driven by family and financial obligations. FS has a strong positive influence on RI (β = 0.576, p < 0.001) and moderates the EE–RI link (β = 0.102, p = 0.007), indicating its buffering role against emotional strain. Overall, the study highlights that balancing transactional leadership with supportive resources and structured recovery policies is crucial for sustaining crew retention in the maritime industry.